2008
DOI: 10.1159/000129635
|View full text |Cite
|
Sign up to set email alerts
|

PGK1 a Potential Marker for Peritoneal Dissemination in Gastric Cancer

Abstract: Background/Aims: Peritoneal carcinomatosis, which is caused by the dissemination of cancer cells into the abdominal cavity is a frequent finding in patients with primary gastric cancer, and it is associated with a poor prognosis. The mechanisms that mediate peritoneal carcinomatosis in diffuse primary gastric tumours require definition. Methods: We therefore compared the gene expression profile in diffuse primary gastric cancer patients with and without peritoneal carcinomatosis (n=13). Human specimens from co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 26 publications
(47 reference statements)
3
66
0
Order By: Relevance
“…Lastly, expression of PGK1 has been shown to be increased by tissue hypoxia (16), regulated by signaling through the CXCR4 chemokine receptor (19), and elevated in HPV-associated respiratory papillomas (J. A. DeVoti, personal communication) as well as in various human cancers (9,10,20,21).…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, expression of PGK1 has been shown to be increased by tissue hypoxia (16), regulated by signaling through the CXCR4 chemokine receptor (19), and elevated in HPV-associated respiratory papillomas (J. A. DeVoti, personal communication) as well as in various human cancers (9,10,20,21).…”
Section: Resultsmentioning
confidence: 99%
“…[21][22][23] Interestingly, the high expression of PGK-1 is significantly correlated with tumor progression, metastasis and multidrug resistance in various cancers. 21,22,[24][25][26] It has also been reported that the expression of PGK-1 in PCa cells could induce bone formation 27 and that cancer-associated fibroblasts, which showed strong expression of PGK-1, could promote PCa growth, 28 suggesting that PGK-1 plays important roles in PCa development, progression and bone metastasis. In addition, both PGK-1 and AR genes are located within Xqll-Xql3 region and PGK-1 short tandem repeat polymorphism linkage to AR in the expression of miR-29a has been found to be correlated with short survival, more invasive phenotype, and early recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, upregulated expression of PGK-1 in tumors has been correlated with metastatic phenotype of tumor. 22,23,25 Thus, downregulation of PGK-1 through epigenetic regulation by isoflavone could be another molecular mechanism by which isoflavone would be able to inhibit PCa invasion. However, more mechanistic studies are warranted.…”
Section: Methodsmentioning
confidence: 99%
“…In non-small lung cancer, CXCLl2 may be involved in the recruitment of CD4+CXCR4 highCD 69 ce lls to tum or tissue (16). In the peritoneum, the expression of CXCLl2 is associated with an increased metastatic rate and homing of ma lignant ce lls (17)(18). CXCR4 is expressed by non-small ce ll lung cancer tissue (19)(20) and by the A549 lung cancer cell line (21) , and its expression is associated with an increased risk of metasta sis (22)(23) and with resistance to chemotherapy (5).…”
Section: Discussionmentioning
confidence: 99%
“…CXCR4 is expressed by non-small ce ll lung cancer tissue (19)(20) and by the A549 lung cancer cell line (21) , and its expression is associated with an increased risk of metasta sis (22)(23) and with resistance to chemotherapy (5). CXCR4 is also expressed by primary gastric cancer ce lls and by tumor ce lls from peritoneal metastases (17)(18). Thus, CXCL12 may play a role in promoting tumor development or metastasis in an autocrine manner via CXCR4 expressed by tumor cells.…”
Section: Discussionmentioning
confidence: 99%